(3JMQjQ cJGH aGfGdGhS aj GdCTcGd GdcQjIs
(3ChdgG (B:s
(3HYO GdOjHGLI Cbhd HYO MeO Gddg hGdKfGA Ydjg Gfj cfJ GQjO Cf GMQQ GdcJH GdehSheI HGdeJhSWGJ s
(3BNQgG (B:s
(3Gbhd (B: (3CXf Gfg JUMja hdYdg cGfJ efj cGfJ Ph VdY eQHY VdY eQHY Je s
(3Vef eLehY , JQJjHgG (B: 3s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdj (B(1930) s
Keywords: (3eJaQbGJs